2014
DOI: 10.1002/jcph.309
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic and pharmacodynamic analysis of tremelimumab in patients with metastatic melanoma

Abstract: Tremelimumab, a fully human monoclonal antibody specific for human cytotoxic T-lymphocyte-associated antigen 4, has been studied in clinical trials. We have reported the results of population pharmacokinetics for tremelimumab in 654 metastatic melanoma patients. Population estimates (inter-individual variability [IIV]) for pharmacokinetic parameters in a final model were clearance (CL), 0.26 L/day (31.8%) and central volume of distribution, 3.97 L (20.4%). CL was faster in males, patients with higher values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
(49 reference statements)
7
35
0
1
Order By: Relevance
“…The influence of disease activity on mAb pharmacokinetics is inconstant. Five publications reported an increase in mAb clearance with disease activity scores (figure 3, table 1): -Eastern Cooperative Oncology Group (ECOG) is an integer numeral score between 0 (asymptomatic) and 5 (death) in cancer patients that was associated with clearance of pembrolizumab [136] and tremelimumab [137] ; -Psoriasis Area Severity Index (PASI) is a decimal number between 0 (asymatomatic) and 72 (maximal) tha was associated with clearance of efalizumab [92] and guselkumab [138] (anti-IL-23); -Harwey-Bradshaw index (HBI) in Crohn's disease patients is an integer number between 0 (asymptomatic) and 26 (maximal) that was associated with clearance of infliximab. [103] …”
Section: Influence Of Disease Activitymentioning
confidence: 99%
“…The influence of disease activity on mAb pharmacokinetics is inconstant. Five publications reported an increase in mAb clearance with disease activity scores (figure 3, table 1): -Eastern Cooperative Oncology Group (ECOG) is an integer numeral score between 0 (asymptomatic) and 5 (death) in cancer patients that was associated with clearance of pembrolizumab [136] and tremelimumab [137] ; -Psoriasis Area Severity Index (PASI) is a decimal number between 0 (asymatomatic) and 72 (maximal) tha was associated with clearance of efalizumab [92] and guselkumab [138] (anti-IL-23); -Harwey-Bradshaw index (HBI) in Crohn's disease patients is an integer number between 0 (asymptomatic) and 26 (maximal) that was associated with clearance of infliximab. [103] …”
Section: Influence Of Disease Activitymentioning
confidence: 99%
“…A second study (NCT01655888) of similar design (open‐label, single‐arm) was later conducted by the same investigator with a higher dose intensity (10 mg/kg q4w for up to week 24 followed by q12w until disease progression or unacceptable toxicity). The higher dose intensity was motivated by a retrospective exposure–response (E‐R) analysis of data from melanoma failed trials suggesting that higher exposure in patients was associated with higher response rate, coupled with in vitro data showing an interleukin‐2 release enhancement proportional to tremelimumab concentrations from whole blood samples of nine cancer donors . Study NCT01655888 enrolled 29 patients and showed similar efficacy, with a median survival time of 11.3 months (95% CI: 3.4–19.2 months).…”
mentioning
confidence: 99%
“…No subject had measurable HAHA suggesting minimal immunogenicity of tremelimumab after multiple 1-hour intravenous infusions. Taken together, these data indicate that the shorter infusion time did not alter the PK of tremelimumab, since the PK parameters are similar to those after a 5-hour infusion of tremelimumab [5,14]. …”
Section: Resultsmentioning
confidence: 89%